The Influence of Meteorological Parameters on Atmospheric Visibility over Ikeja, Nigeria - D. O. Akpootu; M. I. Iliyasu; W. Mustapha; S. Aruna; S. O. Yusuf (Archives of Current Research International, 2017)
This present study investigates the variation of atmospheric visibility with meteorological parameters of measured monthly average daily visibility, mean temperature, relative humidity, atmospheric pressure, rainfall and wind speed for a period of 12-years over Ikeja, Lagos State, South Western, Nigeria (Latitude 6.58°N, Longitude 3.33°E and altitude 40 m above sea level). The results indicated that the seasonal variation of atmospheric visibility is greater during the rainy season than in the dry season. The best visibility was observed during the rainy season with an average value of 9.73 km in the month of April while the worst visibility was during the dry season with an average value of 5.88 km in the month of January. The results from regular observation of atmospheric visibility for the study area during the period under investigation indicated that the observed visibility ranged between 5.88 ± 1.03 km and 9.73 ± 1.03 km with annual mean of 8.68 ± 1.03 km which implies that the atmosphere is mostly clear. The average atmospheric extinction coefficient computed for the study area is approximately 0.4628 km-1 (4.628 × 10-4m-1). Simple linear regression equation relating the atmospheric visibility and the meteorological parameters were developed from which the regression equation relating atmospheric visibility with relative humidity was recommended based on the coefficient of correlation (R), coefficient of determination (R2), standard error of estimates (SEE) and p-value. The skewness and kurtosis for the atmospheric visibility are negatively skewed with value -1.514 and positive kurtosis (leptokurtic distribution) with value 1.244.